Treatment patterns and outcomes of patients with metastatic non-small cell lung cancer in five European countries: a real-world evidence survey - Hollie Bailey; Adam Lee; Laura Eccles; Yong Yuan; Helen Burlison; Cameron Forshaw; Nebibe Varol (BMC Cancer, 2023)
Abstract Background The landscape of non-small cell lung cancer (NSCLC) therapy is rapidly changing. This analysis aimed to understand patient characteristics, diagnosis and treatment patterns in patients with metastatic NSCLC (mNSCLC) without EGFR and ALK mutations across five European countries. Methods Data were drawn from the Adelphi NSCLC Disease Specific Programme™, a point-in-time survey of oncologists/pulmonologists and their consulting patients in France, Germany, Italy, Spain and UK. Physicians completed record forms (RFs) for the next six consecutive consulting patients with advanced NSCLC, who then voluntarily completed questionnaires. As an oversample, physicians provided a further ten RFs specifically for patients with EGFR-wild-type mNSCLC: five patients diagnosed before March 2020 (pre-SARS-CoV-2 [COVID-19]) and five patients diagnosed from March 2020 (during COVID-19). Only EGFR-wild-type/ALK-wild-type patients were included for analysis. Results Mean (standard deviation [SD]) age for 1073 patients with EGFR-wild-type/ALK-wild-type mNSCLC was 66.2 (8.9) years, 65.2% were male and 63.7% had adenocarcinoma. Level of PD-L1 expression at advanced diagnosis was < 1% for 23.1% of patients, 1–49% for 40.9% and ≥ 50% for 36.0%. Most common first-line (1L) advanced treatment was chemotherapy only (36.9%), immunotherapy monotherapy (30.5%) or immunotherapy + chemotherapy (27.6%). Of 158 patients who had progressed beyond 1L therapy, the mean (SD) time-to-treatment discontinuation was 5.1 (4.3) months; 75.9% of whom completed their 1L treatment as intended. A complete response was achieved by 6.7% and a partial response by 69.2% of patients. Of 38 patients who discontinued 1L treatment early, disease progression was reported for 73.7%. Quality of life (QoL) reported by patients was generally lower than normative reference values. Of 2373 oversample patients, physicians reported management changes for 34.7% due to COVID-19, ranging from 19.6% in Germany to 79.7% in the UK. Immunotherapy was prescribed as 1L NSCLC treatment during COVID-19 for 64.2% (n = 786) of patients and pre-COVID-19, for 47.8% (n = 549). Conclusions Real-world treatment patterns suggest that chemotherapy use remains high despite guidelines recommending immunotherapy-based 1L treatment for mNSCLC. QoL reported by patients was generally lower than population reference values. Not implying causality, 1L immunotherapy use was higher during COVID-19 than pre-COVID-19, and the UK saw the biggest impact to patient management due to COVID-19.